PECULIARITIES OF PHYSICAL THERAPIST COMMUNICATION WITH PATIENTS WHEN PROVIDING REHABILITATION SERVICES - Mezentseva, I. V.; Pavlovych, O. S.; Yarlykova, V. D. (Rehabilitation and Recreation, 2022)
The purpose of the study is to determine the key features of communication with patients in the provision of rehabilitation services. Materials and methods of research: theoretical generalization; analysis; synthesis, etc. Results: the peculiarities of the physical therapist’s communication with patients during the provision of rehabilitation services are disclosed. It is noted that in the process of interaction with the patient, the physical therapist can use both verbal and non-verbal communication. At the same time, verbal communication is dominant. A number of conditions that should be observed during verbal communication with the patient are considered. It was found that non-verbal communication is carried out with the help of facial expressions, gestures, poses, etc. In some cases, it can be more effective than verbal. It is noted that a qualified specialist in physical rehabilitation (therapy) should know when and how to appropriately use various forms of non-verbal communication. The main barriers that can prevent verbal or non-verbal communication between the therapist and the patient are highlighted, in particular: excessive noise in the area of providing rehabilitation services; a long distance between the therapist and the patient; the language used by the therapist; time allocated for communication etc. It is emphasized that for a specialist in the field of physical rehabilitation (therapy), communicative competence is of great importance, because during the performance of his professional duties he has to communicate directly with different people, using verbal and non-verbal means of communication, to be able to establish contact, have a conversation with the patient, listen to him etc. Communication skills and skills that are necessary in the practical activity of a physical therapist are highlighted, namely: understanding and taking into account the individual and psychological characteristics of the patient; the ability to conduct a conversation; the ability to overcome communication barriers; the ability to listen to the patient and give him advice; the ability to show sympathy (empathy), etc. It was concluded that a physical therapist should constantly improve his professional and communication skills, since the effectiveness of rehabilitation largely depends on this.